Autonomous vehicle with internal combustion drive based on the homogeneous charge compression ignition technology. (19th October 2017) - Puškár, Michal; Fabian, Michal; Kádárová, Jaroslava; Blišt'an, Peter; Kopas, Melichar
The actual dynamical development of the information technologies is also typical for the area of automotive industry. The autonomous control technology is moving the motorcars into the mobile robot category. The autonomous mobile robotic vehicles, together with new possibilities offered thanks to the mobility services, are improving not only comfort but also safety of transport. Nowadays, application of the homogeneous charge compression ignition technology represents a great progress made in the field of internal combustion drive, taking into consideration more and more rigorous emission standards. This article deals with principles and architecture of the autonomous control, with hybrid drive systems as well as it analyses advantages of the homogeneous charge compression ignition technology, taking into consideration the obtained experimental results.